Clinical Cases in ENT - Chary, Geetha (Jaypee Brothers Medical Publishers (P) Ltd, 2015)
Clinical Cases in ENT is a concise guide to clinical cases concerning 24 different areas of ENT practice, in a simple question and answer format. The 24 chapters describe each case in detail, followed by relevant questions and answers. The first two chapters concern ontological problems, followed by nasal disorders such as sinonasal polyps and inverted papilloma, and disorders of the throat including vocal nodules, glottic cancer and laryngopharyngeal carcinoma. The concluding chapters feature discussion on thyroid and salivary gland conditions. With contributions from leading experts in the field across a variety of cases, and presented in a simple format, Clinical Cases in ENT serves as a useful reference guide for ENT specialists and trainees in the field. Key Points Clinical cases covering 24 ENT conditions Simple question and answer format Illustrated throughout